Equal or not? Women hold less prestigious roles at respiratory medicine conferences than men. Issue 1 (23rd January 2020) - Raviskanthan, Mayurapriya; Rees, Megan; Douglass, Jo; Sleeman, Katherine; Higginson, Irene; Smallwood, Natasha
The gender imbalance in medicine has been a topic of increasing interest and discussion. There are increasing proportions of graduating female medical students globally, with 41.1% of Australian doctors, 47% of UK doctors and 46% of medical residents in the USA being female [1, 2]. However, in positions of influence, the proportions change, such that in the USA only 21% of medical professors and 16% of medical deans are female [3]. Postulated reasons for this include implicit and unconscious gender bias and fewer promotion opportunities available to women. Analysis of the sex distribution of presenters in national and international conferences in 2017 demonstrates a significantly lower proportion of women in more prominent roles compared with men http://bit.ly/2lGJz02